CYP1A1 Polymorphisms and Risk of Prostate Cancer: A Meta-analysis - Shaik, Abjal Pasha; Jamil, Kaiser; Das, Prabhavathy (Urology Journal, 2009)
Introduction: Two common polymorphisms in cytochrome P450; family 1, subfamily A, polypeptide 1 (CYP1A1); have been implicated as a risk factor of prostate cancer, but individual studies have been inconclusive or controversial. We reviewed studies on CYP1A1 polymorphisms in patients with prostate cancer. Materials and Methods: The strategy searching in the PubMed was based on combinations of prostate cancer, CYP1A1, CYP1A1 gene polymorphism, and genetic susceptibility. The last search update was May 2008. The retrieved articles and their bibliographies of were evaluated and reviewed independently by 2 experts. We shortlisted 19 studies, of which 14 on sporadic prostate cancer were analyzed. Overall, 2573 patients with prostate cancer and 2576 controls were analyzed. Results: The random effects odds ratio was 1.350 (95% confidence interval, 1.110 to 1.641; P = .003) for T/C polymorphism and 1.085 (95% confidence interval, 0.863 to 1.364; P = .49) for A/G polymorphism. The A/G polymorphism was not associated with increased risk of prostate cancer. However, the T/C polymorphism showed conflicting results in different studies, while overall, this polymorphism showed significant effects on the susceptibility to prostate cancer. There was no significant between-study heterogeneity for both polymorphisms with respect to distribution of alleles. Conclusion: This meta-analysis suggests that while the CYP1A1 T/C polymorphism is likely to considerably increase the risk of sporadic prostate cancer on a wide population basis, the A/G polymorphism may not influence this risk. However, the association of polymorphisms may be significant with respect to smoking history, diet habits, ethnicity, and race.